Fast finite-time dynamic surface tracking control of a single-joint manipulator system with prescribed performance. Issue 8 (11th June 2021) - An, Si-Yu; Chen, Ming; Wang, Huan-Qing; Wu, Li-Bing
Abstract : Based on Lyapunov finite-time stability theory and backstepping control strategy, we put forward a novel fast finite-time dynamic surface tracking control scheme for a single-joint manipulator system with prescribed performance. Compared with most of the traditional prescribed performance finite-time control methods, this work uses a new universal asymmetric barrier function and has a faster convergence speed. In addition, our proposed method eliminates the problem of explosion of complexity based on the dynamic surface. The proposed controller ensures that the closed-loop system is finite-time stable, and the output variable tracks the desired output signal at finite time. Meanwhile, the tracking error converges to the prescribed boundary constraints, and all the signals of the closed-loop system are bounded. In the end, a simulation example is presented to demonstrate the effectiveness of the proposed scheme.